162k views
5 votes
Solve using substitution
x=2y-6
y= -3x+17

1 Answer

3 votes

Answer:

(x, y) = (4, 5)

Explanation:

given the 2 equations

x = 2y - 6 → (1)

y = - 3x + 17 → (2)

Either substitute x = 2y - 6 into (2) or y = - 3x + 17 into (1)

substituting y = - 3x + 17 into (1)

x = 2(- 3x + 17) - 6

x = - 6x + 34 - 6

x = - 6x + 28 ( add 6x to both sides )

7x = 28 ( divide both sides by 7 )

x = 4

substitute x = 4 into (2)

y = - 12 + 17 = 5

solution is (4, 5 )


User Cxa
by
6.1k points